Nasotracheal Intubation under Videolaryngoscopy in Mandibular Abscess with Trismus - Albertus Medianto Walujo; I Gde Agus Shuarsedana Putra; I Wayan Widana; Ida Ayu Manik Manuaba (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2022)
Management of a difficult airway is a challenge for every anesthesiologist. Mandibular stiffness, trismus, and facial structural deformities often limit the available airway management options. With a variety of techniques that have been developed today, the management of difficult airways is more optimal than conventional management. One technique that can be used is video laryngoscopy. The authors report a case of nasotracheal intubation by video laryngoscopy in a mandibular abscess patient with trismus. The purpose of this case report is to demonstrate the effectiveness of the video laryngoscopy technique to assist nasotracheal intubation and to add insight for nasotracheal intubation technique in difficult airway conditions, especially trismus. Female, 60-year-old, come with a left mandibular abscess with complicated trismus who was planned for incision and drainage of the abscess. Nasotracheal intubation was performed under video laryngoscopy and during the surgical procedure the patient's vital signs were stable. This case report concludes that video laryngoscopy can be an alternative to conventional techniques and awake fiberoptic intubation in the case of nasotracheal intubation.